Bacterial antibiotic sensitivity pattern from urine of asymptomatic HIV positive pregnant women (2011)
Introduction: Asymptomatic bacteriuria (ASB) in pregnancy with adverse pregnancy outcome has been well documented with Escherichia coli and other gram-negative rods being the common organism associated. However, most of these studies were done in patients without additional immunosuppressant except for pregnancy. However; the additional risk of HIV infection in pregnant woman necessitates the evaluation of the microbial isolates and antibiotic sensitivity pattern from the urine samples of these patients without any symptom. Methods: A prospective cohort study was undertaken among HIV positive pregnant women attending our Antiretroviral clinic between 1st May and 30th September 2007. Information recorded from the patient questionnaire included age, parity, marital status, occupation, and level of education. Culture and antibiotic sensitivity was carried out on aseptically collected urines from the patients. Results: Twenty-five. (15.5%) of the 161 urine samples cultured significantly grew organisms. Four of the urine specimen had, in addition, Candida isolated. The mean age of participants was 30.6 ± 4.3 years .and the modal parity was 2. The mean gestational age at presentation was 27.3± 3.2 weeks. Escherichia coli was isolated in 48%, Proteus in 16:0%, Klebsiella in 8.0%, and Staphylococcus aureus in 28.0%. The antibiotic sensitivity test showed that the organisms were 100% sensitive to ciprofloxacin, 80% sensitive to cefuroxime, 60% sensitive to ofloxacin and augmentin but only 36%, 20%, 8.0% and 4.6% sensitive to co-trimoxazole, amoxycillin, chloramphenicol, erythromycin, nitrofurantoin and gentamycin, respectively. The organisms were 100% resistant to tetracycline and ampicillin. Conclusion: This-study shows that the microbial isolates of the ASB among HIV positive pregnant women are similar to those of HIV-negative counterparts but with varying drug sensitivities.